THE CORRELATION BETWEEN ACADEMIC GUIDANCE, LEARNING MOTIVATION, SELF-LEARNING TO STUDENT’S ACHIEVEMENT OF LEARNING IN VOCATIONAL TECHNOLOGY EDUCATION PALANGKA RAYA UNIVERSITY - Whendy Trissan (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
The university institution is also contributing in preparing learning participants to be able to adapt with their circumstances. A fluctuated-academic achievement possessed by students is actually determined due tothemselves. An academic guidance, self-learning and learning motivation becamethe substantial factor to obtain significant academic performance. This research applied the sample of student from Vocational Technology Education Department, University of Palangka Raya. Moreover, the variable components are consisting to academic guidance, self-learning and learning motivation interconnecting to learning achievement variable. Then, data collecting method is by using observation, interview, questionnaire, and documentation. To process those data, it will be conducted by editing, coding, scoring, and tabulating. The analysis tools in this research are validity test, reliability test, inferential test, F test and T test. After analysing to data, it will be recorded as a descriptive document and report form of final research result. The research result has shown that direct relation coefficient is 1,316 higher than direct relation coefficient of 1,225, thus direct relation coefficient is the recommended track. An academic guidance is mostly dominant factor influencing learning achievements of students